Teachers’ Perception on Reducing Students’ Enrollment at University level in Mathematics in Nepal - Pokharel, Thakur Prasad (Journal of Business and Management, 2023)
Background: Students’ enrollment taking mathematics as a major subject has decreased at the university level in recent years. Difficulty in subject matters, the attitude of students, the learning environment, uses of mathematics knowledge in real life, and existing evaluation systems could influence learners’ enrollments at the university level. The purpose of this study is to identify causes for reducing the learners’ enrollment at a higher level in mathematics. Objective: This study desires to investigate the perception of teachers on the dependent variable as a reduction of students’ enrollment in mathematics and independent variables, namely difficulty in subject matters, the attitude of learners, learning environment, application of mathematics in real life, and existing evaluation systems and find relation and influence. Methodology: This inquiry consists of 109 faculty members with qualifications of master’s degree or above in mathematics based on the survey research design in Pokhara valley and its surrounding. A three-point Likert-scale survey questionnaire, 31 structured questions related to dependent variables and independent variables was made and administered by the researcher to the teachers. Result: This study concluded that reducing learners’ enrollment is remarkably confidently correlated with the attitude of students, learning environment, difficulty in subject matters, and the existence of evaluation patterns. This finding further found that the learning environment and existing evaluation system are directly impacted by reducing the students’ enrollment, but other independent variables do not have an influence on the dependent variable, namely perception towards reduction of student enrolment in mathematics. Conclusion: The learning situation and actual judgment system are highly aff ected by reducing the students’ enrollment at a higher level. These two independent variables should be managed by research to address the learners’ interest and demand within a short time interval as an international system. Further study about the perceptions of teachers in pure mathematics and applied mathematics should be done separately to generalize and validate this finding.